Determination of screw withdrawal resistance of Empty Fruit Bunch Fibre Board - MAHAYUDDIN, NOR AIN SYANIEZA; SAMSUDIN, EMEDYA MURNIWATY (Recent Trends in Civil Engineering and Built Environment, 2022)
The utilization of oil palm for all intents and purposes empty fruit bunch fibre on bio-composite product basically has been found to for the most part replace current kind of substance mainly in wood fibre. EFB particularly available as palm oil and known as one of the important agricultural crops in Malaysia. Furthermore, the contains of the cement ratio on EFB essentially has been exposed to really be the reason for incompatibility issue between cement ratio and EFB Fibre. Relating to this issue, a research has been conducted to find the effect of EFB cement ratio on physical properties and to evaluate the screw withdrawal resistance of EFB cement board and its relationship on physical properties. The design mix ratio for cement fibre fabrications with the selection materials such as cement, water and EFB was selected namely 2:1, 2.5:1 and 3:1. A sample were tested for density, thickness monitoring and screw withdrawal resistance. The sample was analysed after 28 days curing. The effect of screws on withdrawal resistance was investigated using universal screw. Results obtained shows that the optimum ratio that support the screw insertion is 3:1 by using vibration table method.